Biomarkers of eosinophilic inflammation in asthma. (April 2014) - Loutsios, Chrystalla; Farahi, Neda; Porter, Linsey; Lok, Laurence SC; Peters, A Michael; Condliffe, Alison M; Chilvers, Edwin R
<x xml:space="preserve">Abstract</x> Eosinophils are mediators of allergic inflammation and are implicated in the pathogenesis of numerous conditions including asthma, parasitic infections, neoplasms, hyper-eosinophilic syndromes, vasculitic disorders, and organ-specific conditions. Assessing eosinophilic inflammation is therefore important in establishing a diagnosis, in monitoring and assessing response to treatment, and in testing novel therapeutics. Clinical markers of atopy and eosinophilic inflammation include indirect tests such as lung function, exhaled breath condensate analysis, fractional exhaled nitric oxide, serum immunoglobulin E levels and serum periostin. Direct measures, which quantify but do not anatomically localise inflammation include blood eosinophil counts, serum or plasma eosinophil cationic protein and sputum eosinophil levels. Cytology from bronchoalveolar lavage and histology from endobronchial and transbronchial biopsies are better at localising inflammation but are more invasive. Novel approaches using radiolabelled eosinophils with single-photon emission computed tomography, offer the prospect of non-invasive methods to localise eosinophilic inflammation.